Microfluidic Shape Analysis of Non-spherical Graphite for Li-Ion Batteries via Viscoelastic Particle Focusing - Park, Jee In; Hong, Sabin; Jin, Daekwon; Lee, Won Jun; Kim, Kyeong Jin; Lee, Young Ki; Lee, Seung Woo; Ahn, Kyung Hyun; Hwang, Jongkook; Kim, Ju Min (Small, 2024)
The size and shape of graphite, which is a popular active anode material for lithium-ion batteries (LIBs), significantly affect the electrochemical performance of LIBs and the rheological properties of the electrode slurries used in battery manufacturing. However, the accurate characterization of its size and shape remains challenging. In this study, the edge plane of graphite in a cross-slot microchannel via viscoelastic particle focusing is characterized. It is reported that the graphite particles are aligned in a direction that shows the edge plane by a planar extensional flow field at the stagnation point of the cross-slot region. Accurate quantification of the edge size and shape for both spheroidized natural and ball-milled graphite is achieved when aligned in this manner. Ball-milled graphite has a smaller circularity and higher aspect ratio than natural graphite, indicating a more plate-like shape. The effects of these differences in graphite shape and size on the rheological properties of the electrode slurry, the structure of the coated electrodes, and electrochemical performance are investigated. This method can contribute to the quality control of graphite for the mass production of LIBs and enhance the electrochemical performance of LIBs.
Keywords: Cross-slot microchannel; Ion batteries; Lithium ions; Particle focusing; Planar extensional flow; Planar extensional flow field; Size and shape; Slurry rheology; Viscoelastic particle focusing; Viscoelastics; cross-slot microchannel; graphite; lithium-ion battery; microfluidics; planar extensional flow field; slurry rheology; viscoelastic particle focusing